31 Intraosseous access is effective whilst wearing CBRN protective equipment. (21st May 2017) - Collins, T
Abstract : Aim: A cross over study aimed to determine comparisons of success rates and ease-of-use ratings in achieving intraosseous access in both wearing and non-wearing of Chemical, Biological, Radiation and Nuclear (CBRN) personal protective equipment (PPE) in a cadaver model. Methods: Using a cross over study, 8 experienced paramedics inserted an intraosseous (IO) device (Arrow EZ-IO©) into a cadaver specimen wearing their standard pre-hospital clothing. The sample then crossed over and applied CBRN PPE and repeated IO insertions. IO insertion times were recorded and assessed for clinical accuracy both before and after cross over with wearing CBRN PPE. Data collection involved the sample completing a confidential questionnaire assessing self-perceived ease-of-use scores for IO access measured in Likert scales (0–10). Qualitative data was captured following structured focus group interviews. Results: The results found no statistical difference between ease-of-use scores for IO access between wearing or non-wearing CBRN PPE. No difference in determining land marking for IO insertion (M 9 vs 8.75 p=0.726), humeral site insertion (M 9.13 vs 8.75 p=0.593), administration of IO saline flush (M 9.25 vs 8.75 p=0.405), holding and manipulating driver (9.13 vs 8.75 p=0.593) and trocar removal (9.25 vs 8.75 p=0.405). The mean ease-of-use scores were found to be lower in CBRN group but not significant, focus group discussions stated that PPE had some restrictions but effective EZ-IO insertion could still be achieved. Insertion times (25secs SD 3.46 vs 34.38secs SD 4.17 p=0.0002) were statistically longer with wearing CBRN PPE. However, focus group discussion stated that it would take significantly longer to achieve intravenous (IV) access and that IO was an effective and faster option compared to IV during a CBRN incident. Conclusion: Intraosseous access can be effectively and promptly achieved whilst wearing CBRN PPE. IO access took an additional 9.4 s whilst wearing CBRN PPE which can provide fast and efficient vascular access during a CBRN incident. References: Garside J, et al. Intraosseous vascular access in critically ill adults: a review of the literature. Nursing in Critical Care 2016;3:167–177. Suyama J. IO versus IV access whilst wearing personal protective equipment in a hazmat scenario. Prehospital Emergency Care 2007;11:467–472. Conflict of interest: The author is an employee for Teleflex Medical Practicing critical care nurse. Funding: None declared.